2016
DOI: 10.3127/ajis.v20i0.1218
|View full text |Cite
|
Sign up to set email alerts
|

People’s Motivation to Participate in Social Network Sites, Subsequent Behaviours, and Situation Self-Awareness following a Crisis: Evidence from the MH370 Flight Incident

Abstract: As people increasingly integrate social network sites (SNSs) into their daily lives, they also turn to these sites for timely information following crises. To date, few studies have examined the effects of different types of motivation on participatory behaviours within SNSs following crises. In this study, self-determination theory (SDT) is applied to examine how individuals are motivated to participate in SNSs following a crisis and how individuals' participatory behaviours can better assist them understand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 62 publications
(92 reference statements)
0
8
0
Order By: Relevance
“…If an activity requires too much effort, people are less likely to participate in it [80]. Therefore, in line with the findings of Wang [80,81], this paper includes three participatory behaviors, namely information seeking, information sharing, and commenting in SNS.…”
Section: Social Networking Sitesmentioning
confidence: 69%
See 3 more Smart Citations
“…If an activity requires too much effort, people are less likely to participate in it [80]. Therefore, in line with the findings of Wang [80,81], this paper includes three participatory behaviors, namely information seeking, information sharing, and commenting in SNS.…”
Section: Social Networking Sitesmentioning
confidence: 69%
“…The literature has identified that the public participates in SNS during crisis circumstances to stay informed (e.g., [8,46,54]) and to exchange information (e.g., [40,72,81]). These actions can be categorized into three distinctive participatory behaviors [80].…”
Section: Social Networking Sitesmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the critical challenges for user interface (UI) designers has been the question of how to create a desirable UI that can both attract and retain users (Chou, Lai, & Liu, 2013;Kim, Kim, & Han, 2013;Mouakket, 2015;Park, Roman, Lee, & Chung, 2009;Wang, 2016). A new, innovative UI for social networking apps may have a better opportunity of attracting user attention and subsequently increase the rate of revisiting.…”
Section: Introductionmentioning
confidence: 99%